THE INFLUENCE OF ISLAMIC WORK ETHIC AND ORGANIZATIONAL CULTURE ON THE EMPLOYEES PERFORMANCE OF PT. BFI FINANCE SHARIAH LAMPUNG - efrina, lisa (Fakultas Ekonomi dan Bisnis - Universitas Syiah Kuala, 2019)
Abstract This study aims to investigate the influence of Islamic work ethics and organizational culture on employee performance at PT. BFI Finance Syariah Lampung. All employees of PT. BFI Finance Syariah Lampung were selected as the respondents of this study and then analyzed using multiple regression analysis. The results of the research showed that the application of the Islamic work ethicss positively influenced the performance of the employees. On the other hand, the culture of organization negatively affected the performance of employees. Thus, to further promote employee performance, the Islamic work ethics should be thoroughly implemented and cultural organization should be restructured so that would not become a detrimental for employee performance.Keywords: Islamic Work Ethics, Organizational Culture and Employee Performance AbstrakPenelitian ini bertujuan untuk menguji pengaruh etos kerja Islam dan budaya organisasi terhadap kinerja karyawan pada perusahaan multifinance PT. BFI Finance Syariah Lampung. Penelitian ini dilakukan terhadap semua karyawan PT. BFI Finance Syariah cabang Lampung sebanyak 103 orang. Analisis data menggunakan program SPSS dengan analisis regresi berganda. Hasil penelitian menunjukkan bahwa penerapan etos kerja Islam memberikan pengaruh positif terhadap kinerja karyawan. Di sisi lain juga budaya organisasi berpengaruh negative signifikan terhadap kinerja karyawan. Dengan demikian, untuk lebih meningkatkan kinerja karyawan, etos kerja Islami harus diimplementasikan secara menyeluruh dan budaya organisasi harus direstrukturisasi sehingga tidak akan merusak kinerja karyawan Kata kunci: Etos Kerja Islam, Budaya Organisasi dan Kinerja Karyawan